Ensuring the phytosanitary quality of beans, tropical forages and cassava collections in the “future seeds” genebank: reference strain bank - Ramirez Pretelt, Julio Cesar; Niño Jimenez, Diana Patricia; Muñoz Molina, Christian David; Dorado Escobar, Edwin Fabian; Cuervo Ibanez, Maritza; Vélez-Rojas, Katalina (2024)
The Germplasm Health Unit of the Bioversity International Alliance and CIAT (GHU-CIAT) ensures that the germplasm of beans, cassava and tropical forages conserved and distributed nationally and internationally by the Germplasm Genebank, and breeding programs are free of quarantine risk pests and diseases. As part of routine activities, GHU-CIAT detects the presence of phytopathogenic fungi using morphological and molecular techniques. In order to ensure the quality and traceability of the results, the GHU-CIAT has created a reference strains bank with those quarantine fungi that can historically be detected in the germplasm evaluated under laboratory conditions. Initially, fungal isolates were identified and characterized morphologically by using conventional taxonomic keys, including photographs of macro and micro morphological features. Additionally, a protocol for DNA extraction was standardized and using Oxford Nanopore Technology, isolates were sequenced and molecularly characterized. Using this methodology, 40 isolates were obtained corresponding to the following genera: Colletotrichum sp., Phoma sp., Alternaria, Curvularia sp., Bipolaris sp., Pestalotiopsis sp., and Fusarium sp. Finally, the morphologically and molecularly characterized strains were conserved under controlled temperature and luminosity conditions. Having this kind of reference strain ensures the quality of the results obtained in the diagnosis of phytopathogenic fungi and works as a quality control mechanism which to evidence and demonstrate the accuracy in the identification and detection of quarantine fungi. This study strengthens the traceability for the validation of the diagnostic method and additionally provides information about the genetic variability of the different species detected. Keywords: Reference strain, Quarantine, Sequencing, Traceability.